2018
DOI: 10.1021/acschembio.8b00827
|View full text |Cite
|
Sign up to set email alerts
|

Precise Small Molecule Degradation of a Noncoding RNA Identifies Cellular Binding Sites and Modulates an Oncogenic Phenotype

Abstract: Herein, we describe the precise cellular destruction of an oncogenic noncoding RNA with a small molecule—bleomycin A5 conjugate, affording reversal of phenotype and a facile method to map the cellular binding sites of a small molecule. In particular, bleomycin A5 was coupled to a small molecule that selectively binds the microRNA-96 hairpin precursor (pri-miR-96). By coupling of bleomycin A5’s free amine to the RNA binder, its affinity for binding to pri-miR-96 is >100-fold stronger than to DNA and the compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 46 publications
3
65
0
Order By: Relevance
“…The first example of using small molecule-bleomycin conjugates to cleave miRNAs came from Li et al, 177 in which they used a heterodimeric-bleomycin A5 conjugate to target oncogenic pri-miR-96. Both the bleomycin derivative and its site of conjugation to the small molecule were carefully selected.…”
Section: Targaprimir-96-bleo (Tgp-96-bleo): Targeted Cleavage Of Pri-mentioning
confidence: 99%
See 2 more Smart Citations
“…The first example of using small molecule-bleomycin conjugates to cleave miRNAs came from Li et al, 177 in which they used a heterodimeric-bleomycin A5 conjugate to target oncogenic pri-miR-96. Both the bleomycin derivative and its site of conjugation to the small molecule were carefully selected.…”
Section: Targaprimir-96-bleo (Tgp-96-bleo): Targeted Cleavage Of Pri-mentioning
confidence: 99%
“…47 To further improve bioactivity, a small molecule cleaver was synthesized by conjugating TGP-96 to bleomycin A5 (TGP-96-Bleo) via the C-terminal amine in the traditional DNA-binding domain of bleomycin A5, thus disrupting key interactions necessary for DNA recognition (Table S1, ESI †). 177 As bleomycin A5 has been shown to cleave AU base pairs, 175 and pri-miR-96 has AU base pairs in close proximity to TGP-96's binding site, this conjugation strategy had a high potential for success.…”
Section: Targaprimir-96-bleo (Tgp-96-bleo): Targeted Cleavage Of Pri-mentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al then reported that the alkaloid sophocarpine antagonized Dicer-mediated processing of miR-21 [75]. Later on, a bleomycin A5 conjugate, which selectively inhibits Drosha processing of pri-miR-96, was discovered and found to upregulate the miR-96 pro-apoptotic target FOXO1, inducing breast cancer cell death [76]. Interestingly, Costales et al identified a SM with overlapping affinity for the precursors of both miR-515 and miR-885, which share a common target motif; this compound was optimized to bind only miR-515 by Inforna, a computational approach that drives sequence-based design of SM targeting structured RNA [77], leading to the Targaprimir-515 molecule [78].…”
Section: General Strategies For Targeting the Ncrnasmentioning
confidence: 99%
“…In 2018, Li et al described a novel small molecule, bleomycin A5 conjugate, which selectively binds to the precursor of miR-96 106 ( Fig. 2A).…”
Section: Mirnasmentioning
confidence: 99%